Address at the opening of the fortieth session - McDonnell, James (Statistical and Social Inquiry Society of Ireland, 1887)
The Statistical Society has now been in existence for thirty-nine years. In its youth it enjoyed a much larger share of popularity than has latterly been extended to it. This was due in a great degree to the fact, that at the commencement of its career it numbered among its members some very remarkable men. Archbishop Whately, Judge Longfield, and Professor Cairns may be named amongst those who contributed valuable papers upon the leading economic questions of the day.
Read, Friday, 19th November, 1886
Keywords: Irish legislation; Critique of existing legislation; 314.15